The dinosaur hunter - Hickam, Homer H., 1943- (Thomas Dunne Books/St. Martin's Press, 2010)
Soon after paleontologist Norman "Pick" Pickford happens on a discovery in Montana that could prove to be revolutionary, a menacing visitor is murdered and Mike Wire, retired L.A. homicide detective and ranch foreman, realizes that the fossils may be worth killing for.